Developmental and extracellular matrix-remodeling processes in rosiglitazone-exposed neonatal rat cardiomyocytes. (April 2014) - Paolini, Paul; Pick, Daniel; Lapira, Jennifer; Sannino, Giuseppina; Pasqualini, Lorenza; Ludka, Colleen; Sprague, L James; Zhang, Xian; Bartolotta, Elesha A; Vazquez-Hidalgo, Esteban; Barba, David Torres; Bazan, Carlos; et al.
Objective: The objective of this study was to investigate the effects of rosiglitazone (Avandia ® ) on gene expression in neonatal rat ventricular myocytes.Materials & methods: Myocytes were exposed to rosiglitazone ex vivo . The two factors examined in the experiment were drug exposure (rosiglitazone and dimethyl sulfoxide vs dimethyl sulfoxide), and length of exposure to drug (½ h, 1 h, 2 h, 4 h, 6 h, 8 h, 12 h, 18 h, 24 h, 36 h and 48 h).Results: Transcripts that were consistently expressed in response to the drug were identified. Cardiovascular system development, extracellular matrix and immune response are represented prominently among the significantly modified gene ontology terms.Conclusion: Hmgcs2, Angptl4, Cpt1a, Cyp1b1, Ech1 and Nqo1 mRNAs were strongly upregulated in cells exposed to rosiglitazone. Enrichment of transcripts involved in cardiac muscle cell differentiation and the extracellular matrix provides a panel of biomarkers for further analysis in the context of adverse cardiac outcomes in humans. Original submitted 15 November 2013; Revision submitted 14 February 2014